Retrospective analysis of dietary fat quality and cardiovascular disease risk markers in middle-aged adults - Zhang, Yongbo; Wang, Fengling; Huang, Bingsen; Li, Miaomiao; Du, Changchun (Frontiers in Nutrition, 2025)
BackgroundThe quality of fat in food affects the cardiovascular system by means of inflammatory and lipid pathways.ObjectiveTo assess the relationship among middle-aged persons’ cardiovascular disease (CVD) risk indicators and the composition of their dietary fat.MethodologyTwo hundred adults (aged 40–65) from the Henan Provincial Chest Hospital’s databases were incorporated in this retrospective, hospital-based observational investigation. Dietary consumption information was taken from food frequency questionnaires that had been filled out and were kept in medical records. Employing the unsaturated-to-saturated fatty acid proportion (UFA:SFA), dietary fat composition was measured and subjects were separated into tertiles. Anthropometric variables, lipid levels (total cholesterol, LDL-C, HDL-C), and inflammation levels (hs-CRP) were obtained from pre-existing laboratory and hospital records.ResultsIn comparison to the lowest tertile, the highest UFA:SFA tertile had greater HDL-C (+8.29 mg/dL, d = 1.54), decreased TC (−30.33 mg/dL, d = 2.86), LDL-C (−24.73 mg/dL, d = 2.67), and hs-CRP (−1.28 mg/L, d = 2.53; all p < 0.001).ConclusionBetter lipid and inflammatory levels were associated with higher dietary fat quality, highlighting the significance of substituting unsaturated fats for saturated fats as a CVD prevention measure. However, prospective or interventional research are required to investigate causal effects, as these results are observational and demonstrate association rather than causality.